Granulomatosis with polyangiitis (Wegener's) presenting as the right ventricular masses: A case report and review of the literature. - Mojgan Mortazavi; Hamid Nasri (Society of Diabetic Nephropathy Prevention, 2012)
Background: Granulomatosis with polyangiitis (Wegener's) is a systemic necrotizing vasculitis. Cardiac involvement in Wegener's has rarely been reported. In this study the echocardiographic findings of granulomatosis with polyangiitis (GPA) in a patient is described. Case Presentation: The case was a 45 years old man admitted to the hospital with a 3 months history of persistent fever and sinusitis. Mild left and right ventricular enlargements as well as three small masses in the right ventricular cavity were identified in echocardiography. One mass was attached to the tricuspid valve and the other two masses were attached to the right septum. Pulmonary artery hypertension (45mmHg) was also reported. The masses responded dramatically to plasma exchanges in combination with steroid therapy, followed by oral cyclophosphamid and low-dose steroid therapy. In the kidney biopsy, 8 out of 11 golomeruli contained fibrous crescents along with sclerotic lesions. Spleen has 140 mm diameter with multiple echo-free lesions and coarse parenchyma in abdominal ultrasound. Serum C-ANCA=671, P-ANCA=1.7 (normal= up to 15U/mL). The diagnosis of granulomatosis with polyangiitis (Wegener's) was established. Conclusions: Presence of three small masses in right ventricular cavity and pulmonary artery hypertension in association with the spleen lesions were an uncommon presentation of GPA. GPA should be considered in the differential diagnosis of any nonspecific illnesses with cardiac involvement.